An Analysis of Maxillary Anterior Teeth Crown Width-Height Ratios: A Photographic, Three-Dimensional, and Standardized Plaster Model's Study. (7th February 2022) - Ahmed, Naseer; Halim, Mohamad Syahrizal; Aslam, Ayesha; Ghani, Zuryati Ab; Safdar, Jawad; Alam, Mohammad Khursheed
Abstract : Objective . To analyze the width and height ratios of maxillary anterior teeth at different crown levels through photographs, 3D, and plaster dental model techniques in a subset of the Pakistani population. Material and Methods . This clinical study consisted of 230 participants. The maxillary impression, standardized photographs, and models were constructed for crown width and height analysis. The SPSS version 25 was used for statistical analysis. Descriptive statistics were carried out for mean, standard deviation, and percentage calculation of teeth width and height, gender, and age of participants. Paired t -test analysis was carried out to compare the dependent variables (teeth size, width, and height ratios) with independent variables (techniques applied, side disparity). A p value of ≤ 0.05 was considered statistically significant. Results . The mean width and height of maxillary anterior teeth obtained through photographs, 3D, and plater models were statistically different. The 3D dental model analysis showed reliable and accurate results. The mean width and height ratio of teeth were different on both sides of the arch. There was a significant difference (p = 0.001 ) in crown width-height ratios at different crown levels. Conclusion . The width and height ratios in the studied population were different at various crown levels. The dimensions of teeth varied from the incisal to the cervical part of the crown. Hence, rather than relying on a single, fixed ratio of 78% to 80% suggested by researchers for anterior teeth, the clinician should adopt different crown width-height ratios to restore teeth with the optimum esthetic outcome.